A REMOTE SENSING ANALYSIS OF VEGETATION DYNAMICS IN THE DRYLAND ECOSYSTEM OF SOKOTO CLOSE-SETTLED ZONE, NORTH-WESTERN NIGERIA - Abubakar, M. J. (FUDMA JOURNAL OF SCIENCES, 2023)
Understanding the vegetation dynamics is very essential for the protection and management of ecological environment especially in the dryland areas. In this paper, remote sensing satellite data and GIS analyses were used to monitor and assessed vegetation dynamics in the Sokoto Close-settled Zone, North-western Nigeria from 2001 to 2016. The objectives of the paper are threefold viz: to measure the extent and the trend of vegetation change; to determine the role of different drivers responsible for vegetation change and to discuss the implications of the observed changes on the ecosystem and the livelihoods of people in the area. The result revealed a gradual but persistent decline in the spatial distribution of vegetation cover from 66% in 2001 to 51% in 2016. Vegetation productivity also declined from 0.71 in 2001 to 0.42 in 2016. Correlation analysis shows that rainfall has a positive while population a negative relationship with the vegetation change. Therefore, deceasing rainfall and increasing population are the major factors of vegetation decline in the area. This has drastically affects the capacity of the ecosystem to provide essential goods and services such as food, water supply and pasture for livestock, with varied socio-economic consequences to the inhabitants of the area.
Keywords: Remote Sensing; Vegetation Change; Dryland; Ecosystem.